2017
DOI: 10.1007/s11121-017-0759-3
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-Pituitary-Adrenal Reactivity to Acute Stress: an Investigation into the Roles of Perceived Stress and Family Resources

Abstract: Objective Rurally situated African Americans suffer from chronic exposure to stress that may have a deleterious effect on health outcomes. Unfortunately, research on potential mechanisms that underlie health disparities affecting the African American community has received limited focus in the scientific literature. This study investigated the relationship between perceived stress, family resources, and cortisol reactivity to acute stress. Method A rural sample of African American emerging adults (N = 60) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 71 publications
(63 reference statements)
1
24
0
Order By: Relevance
“…In addition, evidence suggests that derangements in stress-elicited responses (allostatic load "wear and tear") from cumulative stress exposure, particularly extreme, unpredictable, and social threats, may result in hypothalamicpituitary-adrenocortical axis dysregulation. This has been shown to lead to blunted peak cortisol reactivity to acute stress in blacks, 51 which over time is a direct biological pathway to insulin resistance. 20,51 This is relevant to our demonstrated association of increased stress from MLEs with poor glycemic control, which could profoundly contribute to the significant disparity in ideal FPG status among blacks compared with whites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, evidence suggests that derangements in stress-elicited responses (allostatic load "wear and tear") from cumulative stress exposure, particularly extreme, unpredictable, and social threats, may result in hypothalamicpituitary-adrenocortical axis dysregulation. This has been shown to lead to blunted peak cortisol reactivity to acute stress in blacks, 51 which over time is a direct biological pathway to insulin resistance. 20,51 This is relevant to our demonstrated association of increased stress from MLEs with poor glycemic control, which could profoundly contribute to the significant disparity in ideal FPG status among blacks compared with whites.…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown to lead to blunted peak cortisol reactivity to acute stress in blacks, 51 which over time is a direct biological pathway to insulin resistance. 20,51 This is relevant to our demonstrated association of increased stress from MLEs with poor glycemic control, which could profoundly contribute to the significant disparity in ideal FPG status among blacks compared with whites. 3,52 It is plausible that vulnerability to tobacco use is also closely linked to the stress dysregulation phenomenon across acute and chronic (hence, cumulative) stress dimensions, because these measures were associated with decreased likelihood of reaching intermediate/ideal smoking levels.…”
Section: Discussionmentioning
confidence: 99%
“…Examining both risk and protective processes within Mexican Amer- Table 3. Parameter estimates for the effects from cultural orientation variables to family conflict and from family conflict to the growth factors of cortisol responsivity to ican youth fills an important knowledge gap because they are a vastly understudied population in psychobiological research (Luecken et al, 2013;Obasi et al, 2015Obasi et al, , 2017 and because such studies stand to inform about basic underlying processes related to cultural influences on stress and adaptation. Addressing this gap, the present study found that Mexican American adolescents' cultural orientation significantly altered their cortisol reactivity to an acute laboratory stressor, but this was not mediated by family-related risk (conflict) or protective (familism) resources.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that family conflict was associated with blunted cortisol reactivity emphasizes the costs of cortisol hypoarousal. Within rural African Americans, Obasi et al (2017) found that blunted reactivity to the Trier Social Stress Test was linked with greater stress and lower family support within a minority sample. We draw from Mangold et al’s (2010) research on the cortisol awakening response (another HPA measure in which blunted levels may indicate lack of malleability or physiological flexibility) in order to interpret cortisol hypoarousal in Mexican Americans.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that there is increased secretion of salivary stress biomarkers under different stress conditions, such as during army boot camp (31,32) and challenging mental tasks (33). For example, Obasi and colleagues (2017) reported that cortisol levels increased in response to a controlled laboratory inducement of acute stress in a sample of rural African American adults (33). However, relatively few studies have examined biomarkers of stress measured by cortisol and other salivary biomarkers among sexual minority groups (34)(35)(36)(37)(38).…”
Section: Introductionmentioning
confidence: 99%